Characterization of binding by repaglinide and nateglinide with glycated human serum albumin using high‐performance affinity microcolumns. Issue 23 (3rd October 2022) - Ovbude, Susan T.; Tao, Pingyang; Li, Zhao; Hage, David S.
Abstract : High‐performance affinity microcolumns were used to characterize binding by the anti‐diabetic drugs repaglinide and nateglinide with normal and glycated forms of human serum albumin. The microcolumns contained only nmol amounts of protein and provided a detailed analysis of these drug interactions with good precision and in a matter of minutes per experiment. The overall binding by repaglinide to normal and glycated albumin fits a model with two types of binding sites: a set of one or two moderate‐to‐high affinity regions and a larger set of weaker regions with association equilibrium constants of ∼10 5 and 10 3  M −1, respectively, at pH 7.4 and 37°C. Competition studies gave site‐specific association constants for repaglinide and nateglinide at Sudlow site I of 4.2 × 10 4 and 5.0 × 10 4  M −1 for normal albumin, with a decrease of 26%–30% being seen for nateglinide with glycated albumin and no significant change being noted for repaglinide. At Sudlow site II, repaglinide and nateglinide had association constants for normal albumin of 6.1 × 10 4 and 7.1 × 10 5  M −1, with glycated albumin giving an increase in the association constant at this site for repaglinide of 1.6‐ to 1.8‐fold and a decrease for nateglinide of 51%–58%.